2014
DOI: 10.1186/preaccept-8565849481270705
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome sequencing reveals altered long intergenic non-coding RNAs in lung cancer

Abstract: Background: Long intergenic non-coding RNAs (lncRNAs) represent an emerging and under-studied class of transcripts that play a significant role in human cancers. Due to the tissue-and cancer-specific expression patterns observed for many lncRNAs it is believed that they could serve as ideal diagnostic biomarkers. However, until each tumor type is examined more closely, many of these lncRNAs will remain elusive. Results: Here we characterize the lncRNA landscape in lung cancer using publicly available transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
108
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 42 publications
3
108
0
Order By: Relevance
“…Our computational analysis confirmed previous reports that CCAT1 is altered in CRC, 31 LUAD, 34 and LUSC 34 ( Fig. 6A).…”
supporting
confidence: 81%
See 3 more Smart Citations
“…Our computational analysis confirmed previous reports that CCAT1 is altered in CRC, 31 LUAD, 34 and LUSC 34 ( Fig. 6A).…”
supporting
confidence: 81%
“…Onco-lncRNA-21, also known as FENDRR, has been implicated in a lethal lung development disorder 35 and lung cancer. 34 As shown in Figure 3C, in addition to LUAD and LUSC, oncolncRNA-21 expression levels are also significantly downregulated in BLCA and CRC. Taken together, we have reconfirmed altered expression of lncRNAs previously implicated in cancer interspersed among many uncharacterized lncRNAs that are recurrently altered across multiple cancer types.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…In this study we identified 1041 miRNAs altogether in the extracellular vesicle and cell samples studied, which are more than most array systems would detect. [22][23][24][25][26][27]42,43 Further, comparison among expression of miRNAs is possible with deep sequencing approaches, if the absolute number of copies in the sample can be quantified. 44 In this study, by using the Quantile normalization method for all samples, miRNA expression showed positive relationship between the samples, although many detected miRNA are unique in the different subsets of vesicles ( Fig.…”
Section: Discussionmentioning
confidence: 99%